Gambaran Histopatologik Aorta Tikus yang Diberikan Durian (Durio zibethinus Murr.) Setelah Pemberian Lemak Babi - Limpo, Jessica P.; Lintong, Poppy M.; Loho, Lily (Universitas Sam Ratulangi, 2018)
Abstract: Hyperlipidemia is a major trigger factor of atherosclerosis. Durian (Durio zibethinus Murr.) has a complex nutrient content such as high energy that can cause obesity resulting in hyperlipidemia. Recently several studies suggest that durian consists of vitamin C, vitamin E, carotenoids, and flavonoid as antioxidants that can inhibit the atherosclerosis process. This study was aimed to obtain the effects of durian administration on histopathologic features of Wistar rat aorta induced by lard. This was an experimental laboratory study using 26 male Wistar rats divided into four groups, as follows: group A (5 rats) without treatment; group B (7 rats), induced with 2 ml of lard twice a day for 28 days; groups C (7 rats), induced with lard for 28 days and then was continued with no treatment for 14 days; group D (7 rats), induced with lard for 28 days and was continued with the administration of durian 3,6g/day for 14 days. The results showed that there was a decrease in the number of foam cells in the group that was administered with durian compared to the groups without durian administration. Conclusion: The histopathological features of Wistar rats administered with durian (Durio zibethinus Murr.) after induced with lard showed a smaller number of foam cells compared to the groups without durian administration.Keywords: lard, atherosclerosis, foam cell, durianAbstrak: Hiperlipidemia merupakan faktor pemicu utama terjadinya aterosklerosis. Durian (Durio zibethinus Murr.) memiliki kandungan gizi yang kompleks seperti energi tinggi yang dapat menyebabkan kegemukan dan berimbas pada keadaan hiperlipidemia. Beberapa sumber menyatakan bahwa durian mengandung beberapa jenis antioksidan yang dapat menghambat terjadinya proses aterosklerosis. Penelitian ini bertujuan untuk mendapatkan efek pemberian durian terhadap gambaran histopatologik aorta tikus Wistar yang diberikan lemak babi. Jenis penelitian ialah eksperimental laboratorik, menggunakan 26 ekor tikus Wistar yang dibagi menjadi empat kelompok yaitu kelompok A (5 ekor tikus) tanpa perlakuan; kelompok B (7 ekor tikus) diberikan lemak babi dua kali sehari sebanyak 2ml/kali selama 28 hari; kelompok C (7 ekor tikus) diberikan lemak babi selama 28 hari dilanjutkan tanpa perlakuan selama 14 hari; kelompok D (7 ekor tikus) diberikan lemak babi selama 28 hari dan dilanjutkan dengan pemberian durian sebanyak 3,6g/hari selama 14 hari. Hasil penelitian ini mendapatkan pengurangan jumlah sel busa pada kelompok yang diberikan durian dibandingkan kelompok tanpa pemberian durian. Simpulan: Tikus Wistar yang diberikan durian (Durio zibethinus Murr.) setelah pemberian lemak babi menunjukkan gambaran histopatologik aorta dengan jumlah sel busa yang lebih sedikit dibandingkan dengan yang tanpa pemberian durian.Kata kunci: lemak babi, aterosklerosis, sel busa, durian